Realizations of Promising Speech Act by Students of English as a Foreign Language of Semarang State University - Mubais, Ahmad; Sofwan, Ahmad (English Education Journal, 2018)
To communicate with others requires the ability of communicative competence. The communicative competence covers discourse competence, linguistic competence, pragmatic competence, socio cultural competence and lastly actional competence. Pragmatic competence is such a communicative competence which is important to study in order to fill the gap among the speakers, especially students of English as a foreign language. The gap among the speakers of different languages can be decreased by the study of speech act in various languages and perspectives. The focus of this study is the analysis of pragmatic study that focuses on promising speech act delivered by Students of English as a Foreign Language of Universitas Negeri Semarang. The objectives of his study are concentration on analysing the realization of promising speech act by the students, the probable factors that influence the students in realizing promising speech act, how those factors influence students to realize a promise and what dominant strategy used by the students. This research is qualitative descriptive research. The source data of this research is document. In order to collect the data, there are two methods used in this research; DCT and Role play methods. The types in analysing the data are transcribing, coding, classifying and interpreting. The subjects of the research are 20 students of English as a Foreign Language of Universitas Negeri Semarang at sixth and eighth semester. There are 480 utterances of promising speech act produced by the students from the DCT and Role play data elicited. Based on the analysis, the study reveals that the students applied future action, promise-to-act and predictive assertion strategy to realize the promise. The probable factors that influence students to realize the promise are distance, dominance and imposition. Actually, those factors (distance, dominance and imposition) are not primary factors that impose the students in realizing the promise. Some situations with different combination of social parameters deliver different strategy. The different combination of the three factors in situation given and interference of students’ native language and pragmatic transfer in the language learning process also affects the respondents in realizing a promise strategy. The dominant strategy used by the students is future action strategy.